Perancangan Busana Ready-to-Wear dengan Konsep Recycled Fashion dengan Teknik Tie Dye - Langi, Kezia Clarissa; Laurey, Bruce; Janty, Tan Indra (Moda : The Fashion Journal, 2023)
Recycled fashion is a sustainable way to recycle waste resources and solve global pollution problems. This process has attracted worldwide attention to partially solve the problem of discarding used clothing and dead stock of clothing. This final work utilizes sale stock from department store. The products on sale are products that are no longer of interest to buyers. In increasing the selling value of the product, the tie dye technique is used. This ready-to-wear collection is intended for men aged 20-30 years for casual use. This collection consists of 4 looks with oversized silhouettes. This collection shows that creative product designs from recycled fashion contribute to a sustainable and green environment.